Financial wellness among FELDA and RISDA employees / Shah Amiruzaini Badhrul Hisham and Muhamad Helmi Muhamad Ali - Badhrul Hisham, Shah Amiruzaini; Muhamad Ali, Muhamad Helmi (2013)
The purpose of this study was to examine determinants that influence financial wellness. The results of this study can be used for better understanding on the relationships between and among determinants of financial wellness by highlighting the relationships among demographic characteristics, financial literacy, financial behaviors, financial stress, and financial wellness. Samples were selected using multi-stage sampling technique among employees in public sectors. A total of 100 completed questionnaires were analyzed using path analysis to identify direct and indirect effects on financial wellness. The findings identified that financial wellness were financial behaviors, financial stress level, financial literacy, income, gender, marital status, home ownership, and education had either a direct or indirect effect on financial wellness. Age and ethnicity were found not significantly affect the financial satisfaction.